11C-Choline-Pet Guided Stereotactic Body Radiation Therapy for Lymph Node Metastases in Oligometastatic Prostate Cancer. (21st October 2017) - Franzese, Ciro; Lopci, Egesta; Di Brina, Lucia; D'Agostino, Giuseppe Roberto; Navarria, Pierina; Mancosu, Pietro; Tomatis, Stefano; Chiti, Arturo; Scorsetti, Marta
ABSTRACT: Introduction : aim is outcome of 11C-Choline-PET guided SBRT on lymph node metastases. Materials and methods : patients with 1 – 4 lymph node metastases detected by 11C-choline-PET were treated with SBRT. Toxicity, treated metastases control and Progression Free Survival were computed. Results : twenty-six patients, 38 lymph node metastases were irradiated. No grade ≥ 2 toxicity. Median PSA-nadir after RT was 1.02 ng/mL. Post-treatment 11C-Choline-PET showed metabolic complete response in 17 metastases (44, 7%), partial response in 9 metastases (38%). Conclusion : SBRT is effective and safe for lymph node metastases. PET is important in identification of gross tumor and evaluation of the response.